Picnic time - Hunt, Roderick; Brychta, Alex (Oxford : Oxford Univ. Press., 2014)
Read with Biff, Chip and Kipper is designed to help children learn to read. Created by reading experts and based on current teaching practice, the lively stories, humorous illustrations and clear progression will ensure your child succeeds.